2015
DOI: 10.5539/ass.v11n24p62
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Teachers’ Career in Relationship to OCB and Justice: A Study in Malaysia

Abstract: This study is conducted to examine the relationship between organizational citizenship behaviour (OCB) and teachers' Career Advancement (CA) in the context of the Malaysian teachers. Two aspects of teachers' CA such as number of promotion (NOP) and career satisfaction (CS) have been investigated in this study. This study also explores the roles of justice (distributive justice, procedural justice, interactional justice) as moderator in the relationship between OCB and CA. The data was gathered through mail sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Every organization needs the personnel to reflect more positive behaviors beyond their work roles. It means that the organization will have the personnel with tie and loyalty in the organization and willing to make the organization outstanding than other organization and to promote strength of the organization (Ekowati, Troena, & Noermijati, 2013;Saraih, Ali, & Khalid, 2015). Organizational citizenship behavior is what a person can share with the colleagues to help in operational problems.…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Every organization needs the personnel to reflect more positive behaviors beyond their work roles. It means that the organization will have the personnel with tie and loyalty in the organization and willing to make the organization outstanding than other organization and to promote strength of the organization (Ekowati, Troena, & Noermijati, 2013;Saraih, Ali, & Khalid, 2015). Organizational citizenship behavior is what a person can share with the colleagues to help in operational problems.…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…Organizational justice also considers treatment of people too (Folger & Cropanzano, 1998;Sheppard, Lewicki, & Minton, 1992). From the review of the literature it was found that justice is the expectation of the staff on the returns from the organization as fair consideration of equity with a valid and transparent criteria that can be checked (Saraih et al, 2015). When the personnel perceives justice in the organization or from leader, it brings satisfaction and, confidence in the leader and the organization and the willingness to work with full efforts toward the organizational goal (Colquitt, 2012;Khan & Rashid, 2015;Zeinabadi & Salehi, 2011).…”
Section: Justicementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is argued that the teacher's belief towards the performance appraisal system can be one of the factors that contribute in motivate most of the qualified teachers for the post of excellent teachers to apply for the position. From the study of Saraih et al (2015) and Hoque et al (2012) based on their interviewed information, a few factors were found demotivate qualified teachers for the post of Excellent Teachers that are: 1) the Excellent Teachers were not allowed to return as regular teacher 2) they can be transferred as per requirement from the Ministry of Education. In line with these two factors, no further research was conducted to support the significance of the relationship towards the behavior (Saraih et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…From the study of Saraih et al (2015) and Hoque et al (2012) based on their interviewed information, a few factors were found demotivate qualified teachers for the post of Excellent Teachers that are: 1) the Excellent Teachers were not allowed to return as regular teacher 2) they can be transferred as per requirement from the Ministry of Education. In line with these two factors, no further research was conducted to support the significance of the relationship towards the behavior (Saraih et al, 2015). Hence, the current study included Belief towards Performance Appraisal System (BTPAS) as one of the predictors of intention to apply for promotion, thus indicate that BTPAS is one of the contributors in predicting intention to apply for promotion among teachers in Malaysia, in general.…”
Section: Discussionmentioning
confidence: 99%